2008
DOI: 10.1088/0953-8984/20/44/445001
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen adsorption, dissociation and diffusion on the α-U(001) surface

Abstract: First-principles pseudopotential plane-wave calculations based on density functional theory and the generalized-gradient approximation have been used to study the adsorption, dissociation, and diffusion of hydrogen on the α-U(001) surface. Weak molecular chemisorption was observed for H 2 approaching with its molecular axis parallel to the surface. The optimization of the adsorption geometries on the threefold hollow sites yields final configurations with H 2 molecules moving towards the top site at both cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 25 publications
5
29
4
Order By: Relevance
“…This phenomenon ascribes that the interaction of H 2 with the surface on the top site is much smaller than the other three adsorption configurations. This result is consistent with the adsorption energies of H 2 molecule on U(001) surface . In the same adsorption configurations, the d 12 has much larger shrinkage than the d 23 because of the immediate interaction of H 2 molecule with the surface uranium atoms, which strengthens the interaction between the surface and subsurface, and this finally narrows the distances between all the uranium layers.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…This phenomenon ascribes that the interaction of H 2 with the surface on the top site is much smaller than the other three adsorption configurations. This result is consistent with the adsorption energies of H 2 molecule on U(001) surface . In the same adsorption configurations, the d 12 has much larger shrinkage than the d 23 because of the immediate interaction of H 2 molecule with the surface uranium atoms, which strengthens the interaction between the surface and subsurface, and this finally narrows the distances between all the uranium layers.…”
Section: Resultssupporting
confidence: 83%
“…[10] Nie investigated on the adsorption, dissociation, and diffusion of H 2 on the α-U(001) surface by DFT calculations. [11] Nie's research showed that the hybridization of U 5f and H 1s state only occurs when the H 2 molecule is dissociated, which is different from our work. The different research results can be due to the improved calculations by DFT in the latter.…”
Section: Introductioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Uranium easily reacts with hydrogen [8], oxygen [9], and water [10] due to its lively chemical nature. These reactions take place on the surface and are mainly determined by the nature of the 5f electrons of the surface atoms.…”
Section: Introductionmentioning
confidence: 99%